EFFECTIVENESS OF THE E-PEKEN PROGRAM IN EMPOWERING MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Zahrani, Rheina Adinda; Balahmar, Ahmad Riyadh Umar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of the E-Peken application in empowering Micro, Small, and Medium Enterprises (MSMEs) in Jambangan District, Surabaya City. E-Peken is a digital innovation from the Surabaya City Government designed to expand MSME market access through a local e-commerce platform. Method: This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. Campbell J.P.'s program effectiveness theory is used as the basis for analysis, which includes five main indicators: program success, target success, user satisfaction, input and output effectiveness, and overall goal achievement. Results: The results of the study indicate that the E-Peken application has the potential to increase the visibility and competitiveness of MSME actors, but still faces a number of obstacles such as low digital literacy, lack of training and mentoring, and limited application features. MSME participation is dominated by the culinary sector, while business actors in other sectors feel that they are not yet optimally facilitated. Novelty: The novelty of this research lies in the holistic application of Campbell's effectiveness theory framework to evaluate digital programs based on local economic empowerment, as well as the specific focus on SMEs in Jambangan Subdistrict, which has not been extensively studied. These findings provide concrete recommendations for the government to refine its digital empowerment strategies based on society.